KAJIAN KINERJA GURU UNTUK PENGUATAN KEBERLANJUTAN SEKOLAH VOKASI STUDI PADA SMK NEGERI 1 MOJOSONGO BOYOLALI TAHUN 2024 - Arifah Kurniawati; Edy Purwo Saputro; Lukman Hakim (POLITEKNIK LP3I JAKARTA, 2024)
This research aims to analyze the study of teacher performance for strengthening the sustainability of vocational schools at SMK Negeri 1 Mojosongo Boyolali in 2024. This research method is quantitative. In this study the population used was teachers at SMK N 1 Mojosongo Boyolali totaling 146 teachers. The number of samples in this study was selected based on the Simple Random Sampling technique and calculated by the Slovin formula and obtained a sample of 107 teachers. The data used in this study are primary and secondary data. The data collection technique in this study used a questionnaire. The data analysis technique used in this research is Partial Least Square (PLS) using the help of SMARTPLS Software. PLS-SEM analysis consists of two Outer model and Inner model. The results showed that self-efficacy has a significant positive effect on teacher performance. First, high self-efficacy increases teachers' confidence in their abilities, which has a direct impact on improving performance. Second, self-efficacy also contributes to motivation, where teachers who feel capable tend to be more motivated to teach well. Furthermore, high motivation has a positive effect on teacher performance, facilitating better achievement of teaching goals. Finally, self-efficacy influences teacher performance through work motivation, suggesting that increased self-efficacy can result in stronger motivation, which in turn improves their performance. This confirms the importance of developing self-efficacy in the educational context to achieve optimal results.